The development and management of an educational change innovation: the case of the Institute of Distance Education (IDE) at the University of Swaziland. - Nsibande, Njabuliso H. (My University, 2014)
This research contributes to the on-going search for solutions in the management of distance education in a conventional university. It focuses on the development and management of distance education (DE) in a dual mode university system. A conceptual framework is developed in this study and uses a case study to analyze issues related to the management and development of distance education change as the University of Swaziland (UNISWA) transforms its delivery mode. The conceptual framework was developed to inform the research and questions Were built around the following issues: Origins of distance education at the University of Swaziland at IDE; planning for the introduction and development of distance education;implementation; and evaluation of the programs. The results that merit attention are those that question the nature and form of the leadership and the way distance education was introduced,planned, implemented and monitored at UNISWA.